Recent advances in application of edible coatings for temperate fresh/fresh-cut fruits: a review - Farid Moradinezhad; Nida Firdous (Journal of Horticulture and Postharvest Research)
Purpose: Temperate fruits not only provide essential nutrients but also contribute to the diversity and sustainability of horticultural production systems worldwide. The total production of fruits, increased during the past twenty years. However, postharvest losses of fruits due to spoilage, decay, and physiological deterioration pose a significant challenge to the global food supply chain, which leads to a decline in fruit quantity and quality after harvest. Findings: Edible coatings have emerged as a sustainable solution for extending the shelf life of fruits while reducing postharvest losses. The use of edible coatings is not only environmentally friendly but also addresses consumer demands for natural, safe, and healthy food products obtained through minimal processing. A wide array of edible coating materials is available, each possessing unique properties that influence their effectiveness in preserving fruits. The specific composition and application of edible coatings play a crucial role in their effectiveness in inhibiting microbial growth, reducing enzymatic browning, and maintaining the sensory quality of the fruits. Limitations: No limitations were found. Directions for future research: Future research should focus on exploring and developing new, sustainable, and biodegradable coating materials derived from renewable sources. Additionally, incorporating nanotechnology into edible coatings can enhance their properties, such as improved barrier properties, controlled release of active compounds, and enhanced antimicrobial activity. Continued research and innovation in this area hold significant promise for reducing postharvest losses, improving food security, and promoting sustainable agricultural practices. This review summarizes recent advances in different edible coating materials and their uses in prolonging shelf life and decreasing postharvest losses of important temperate fresh/fresh-cut fruits worldwide.